Development of Rotation Tools for Artistic Gymnastics Sports - Sholeh, Arif Bustaman Sholeh; Soenyoto, Tommy; djunaidi, said (Journal of Physical Education and Sports, 2025)
Many junior male artistic gymnastics athletes have not been able to perform rotational or circular movements on the mushroom apparatus. This research aims to 1) Develop rotational mushroom tools in gymnastics tools for circles. 2) To find out the effectiveness of rotational mushroom tools to improve circular skills. 3) The results of this rotation mushroom development model can be accepted by gymnastics coaches and athletes in Central Java. This development research uses a procedural research method. The approach in this study uses a qualitative approach. The research subjects in this study are male artistic gymnastics athletes (juniors), gymnastics coaches, gymnastics experts/experts. The data collection techniques used in this study are observation (observation), interview, and documentation. Data analysis techniques, namely data reduction, data display, and conclusion drawing/verification. The results of the research are 1) In small-scale trials, problems were found, namely the tool was too high. Experts advise to shorten the size as well as make the bottom flat. 2) The effectiveness of the development of rotation tools can improve the ability of circuits in junior athletes in mushroom tools is proven by observations and data collection carried out by researchers. Several Pengcab gymnastics athletes in Central Java stated that this tool is very helpful for the process of practicing circular movements 3) The results of the model of development of rotation tools for artistic gymnastics athletes can be accepted by coaches and gymnastics athletes in Central Java. This is proven by the support and enthusiasm carried out by several coaches when athletes try to use this rotation tool. The conclusions of this study are 1) Modification of rotation equipment is adjusted to the needs of gymnasts, namely for junior athletes in improving circuit skills in mushroom equipment. 2) The effectiveness of the product modification model of rotation equipment development for artistic gymnastics athletes to improve circuit skills 3) The enthusiasm and response of gymnastics coaches in Central Java is very good